The Prognostic Signature of Head and Neck Squamous Cell Carcinoma Constructed by Immune-Related RNA-Binding Proteins - Ming, Ruijie; Li, Xiangrui; Wang, Enhao; Wei, Jiahui; Liu, Bo; Zhou, Peng; Yu, Wenting; Zong, Shimin; Xiao, Hongjun (Frontiers in Oncology, 2022)
Purpose: To construct a prognostic signature consisting of immune-related RNA binding proteins (RBPs) to predict the prognosis of patient with head and neck squamous cell carcinoma (HNSCC) effectively. Methods: The transcriptome and clinical data of HNSCC was downloaded from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. Firstly, we ascertained the immunological differences in HNSCC, through single sample gene set enrichment analysis, stromal and immune cells in malignant tumor tissues using expression data (ESTIMATE) and cell-type identification by estimating relative subsets of RNA transcripts (CIBERSORT) deconvolution algorithm. Then we used univariate proportional hazard (Cox) regression analysis and least absolute shrinkage and selection operator (LASSO) Cox regression analysis to screen immune-related RBPs and acquired the risk score of each sample. Subsequently, we further investigated the difference in prognosis, immune status, tumor mutation burden in high- and low-risk groups. Finally, the efficacy of immunotherapy was measured by tumor immune dysfunction and exclusion (TIDE) score. Results: We derived 15 immune-related RBPs, including FRMD4A, ASNS, RAB11FIP1, FAM120C, CFLAR, CTTN, PLEKHO1, SELENBP1, CHCHD2, NPM3, ATP2A3, CFDP1, IGF2BP2, NQO1, DENND2D. There were significant differences in the prognostic of patients in the high- and low-risk groups in the training set (P < 0.001) and the validation set (P < 0.01). Furthermore, there were statistical differences between high-risk group and low-risk group in immune cell infiltration and pathway and tumor mutation load (P < 0.001). In the end, we found that patients in the low-risk group were more sensitive to immunotherapy (P < 0.001), and then screened 14 small molecule chemotherapeutics with higher sensitivity to the high-risk group (P < 0.001). Conclusion: The study constructed a prognostic signature of HNSCC, which might would guide clinical immunotherapy in the future.